2022
DOI: 10.1186/s12974-022-02544-5
|View full text |Cite|
|
Sign up to set email alerts
|

Glyphosate infiltrates the brain and increases pro-inflammatory cytokine TNFα: implications for neurodegenerative disorders

Abstract: Background Herbicides are environmental contaminants that have gained much attention due to the potential hazards they pose to human health. Glyphosate, the active ingredient in many commercial herbicides, is the most heavily applied herbicide worldwide. The recent rise in glyphosate application to corn and soy crops correlates positively with increased death rates due to Alzheimer’s disease and other neurodegenerative disorders. Glyphosate has been shown to cross the blood–brain barrier in in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…In our studies, we hypothesized that glyphosate in GBH causes neuroin ammation to impair cognitive function. It has been recently shown that oral administration of glyphosate to mice (125, 250 and 500 mg/kg for 14 days) elevates glyphosate levels (10-50 ng/mg) and tumor necrosis factor-(TNFα) in the brain (Winstone et al, 2022). This study has two important implications: orally administered glyphosate in ltrates the CNS and elevates pro-in ammatory cytokines in the CSF.…”
Section: Discussionmentioning
confidence: 77%
“…In our studies, we hypothesized that glyphosate in GBH causes neuroin ammation to impair cognitive function. It has been recently shown that oral administration of glyphosate to mice (125, 250 and 500 mg/kg for 14 days) elevates glyphosate levels (10-50 ng/mg) and tumor necrosis factor-(TNFα) in the brain (Winstone et al, 2022). This study has two important implications: orally administered glyphosate in ltrates the CNS and elevates pro-in ammatory cytokines in the CSF.…”
Section: Discussionmentioning
confidence: 77%
“…Brain imaging studies have also found that the areas of the brain most vulnerable to the toxic effects of chemicals and other environmental toxins are the pre- and post-central gyri, temporal transverse gyrus, and the calcarine regions. While epidemiologic associations between environmental chemical exposure and AD are still limited, the risk of developing AD in older adults due to neurologic impairments caused by environmental toxins is well established [ 199 , 210 , 211 , 212 , 213 ].…”
Section: Multiple Strategies To Optimize Brain Healthmentioning
confidence: 99%
“…Studies in cell and animal models have revealed alterations in neural pathways and metabolism associated with AD. Neuro-imaging studies have reported associations between exposure to toxic chemicals and white matter volume reduction [ 213 , 214 , 215 ]. Other reported effects include reduced gray matter, larger ventricular volume, and smaller corpus callosum.…”
Section: Multiple Strategies To Optimize Brain Healthmentioning
confidence: 99%
“…In the neuronal tissue, GYP enhances neuronal excitation and loss of neuronal plasticity leads to neurodegenerations [6]. Furthermore, it affects cellular metabolism and causes mitochondrial dysfunctions via free radical generation, release of pro-inflammatory cytokines, and enhance the synthesis & release of glutamate molecules [7,8]. Subsequently, it also causes the dysfunction of the blood-brain barrier (BBB) [9].…”
Section: Introductionmentioning
confidence: 99%